Analisis silang faktor determinan pengelolaan budidaya perikanan berbasis masyarakat di Teluk Bintuni, Papua Barat: peran, kapasitas, dan optimasi masyarakat - N. Silaratubun, Ismi; Bawole, Roni; Holle, Yolanda; Boli, Paulus; Alfarani Bawole, Christover (Program Pascasarjana Universitas Papua, 2026)
ABSTRACT : This study aims to examine expert perceptions regarding the sustainability of aquaculture in Bintuni Bay through a cross-analysis of several key aspects: community participation, awareness of the importance of aquaculture, community involvement in decision-making, capacity building, engagement in monitoring and evaluation, optimization of production and resources, and the distribution of economic benefits. The results indicate a predominance of positive perceptions but also highlight significant challenges related to the quality of participation, equitable distribution of economic benefits, and the effectiveness of monitoring mechanisms. Recommendations are directed toward strengthening institutional capacity, promoting technological innovation, and developing inclusive participatory mechanisms to enhance both social and ecological sustainability.